MUTATIONAL ANALYSIS OF THE ROLE OF THE CARBOXY-TERMINAL REGION OF THE V-ERBB PROTEIN IN ERYTHROID CELL-TRANSFORMATION - LEE, EB; BEUG, H; HAYMAN, MJ (NATURE PUBLISHING GROUP, 1993)
The v-erbB protein encoded by the avian erythroblastosis virus AEV-H is responsible for the transformation of fibroblasts and erythroblasts by this virus. Deletion of amino acids 961-1102, which lie carboxy terminal to the kinase domain of the v-erbB protein, destroys the ability of the virus to transform erythroid cells without severely affecting fibroblast transformation. This region is termed the E-domain and has been postulated to contain a region important for erythroid cell transformation. In-frame deletions of approximately 23 amino acids were introduced throughout the E-domain in an attempt to locate a specific region that was essential for erythroid cell transformation. Several of the deletions gave rise to a partial transformed phenotype, although no single deletion that completely abolished erythroid cell transformation was found. Interestingly, deletion of amino acids 1031-1055 resulted in a superactivated v-erbB protein that was more active for erythroid cell transformation than the wild-type AEV-H v-erbB protein. This indicates that there is a negative regulatory region located within this region that normally partially suppresses the transforming activity of the v-erbB protein for erythroid cells. These data suggest that the E-domain contains both negative and positive regulatory regions that function in erythroid cells, and complete deletion of the region is necessary to abolish erythroid cell transformation.
Keywords: AVIAN ERYTHROBLASTOSIS VIRUS; GROWTH-FACTOR RECEPTOR; SINGLE POINT MUTATION; EGF RECEPTOR; TYROSINE KINASES; GENE-PRODUCT; C-ERBB; IDENTIFICATION; EXPRESSION; MUTANTS